2007
DOI: 10.1165/rcmb.2006-0283rc
|View full text |Cite
|
Sign up to set email alerts
|

NS1 Protein of Influenza A Virus Inhibits the Function of Intracytoplasmic Pathogen Sensor, RIG-I

Abstract: Retinoic acid-inducible gene I (RIG-I) has recently been identified as one of the key intracellular sensors of virus infection. RIG-I binds to cytosolic double-stranded RNA and initiates a signaling cascade that leads to the activation of transcription factors required for expression of type I interferon (IFN-I). Previous evidence suggests that nonstructural protein 1 (NS1) encoded by influenza A virus (IAV) suppresses IFN-I secretion in virus-infected cells by an unknown mechanism. In the present study, we de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
223
0
4

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 266 publications
(239 citation statements)
references
References 15 publications
12
223
0
4
Order By: Relevance
“…For example, the NS1 protein of the influenza A virus inhibits the function of RIG-I, thus downregulating type I IFN expression. 18,19 The V proteins of paramyxoviruses interact with MDA-5 to block its activity, which leads to a reduction in IFN-b promoter activation. 20 The cysteine protease NS3/4A of hepatitis C virus cleaves VISA and the TLR3 adapter protein TRIF, thereby blocking RIG-I-and TLR3-mediated induction of the type I IFNs.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the NS1 protein of the influenza A virus inhibits the function of RIG-I, thus downregulating type I IFN expression. 18,19 The V proteins of paramyxoviruses interact with MDA-5 to block its activity, which leads to a reduction in IFN-b promoter activation. 20 The cysteine protease NS3/4A of hepatitis C virus cleaves VISA and the TLR3 adapter protein TRIF, thereby blocking RIG-I-and TLR3-mediated induction of the type I IFNs.…”
Section: Introductionmentioning
confidence: 99%
“…For example, NS1 blocks 29-59-oligoadenylate synthetase-mediated activation of RNase L (Min & Krug, 2006) and limits the induction of IFN-b (Wang et al, 2000;Ludwig et al, 2002). Furthermore, NS1 binds to and inhibits the cytoplasmic dsRNA sensor retinoic acidinducible gene product I (Guo et al, 2007;Mibayashi et al, 2007) and blocks protein kinase R-mediated inhibition of protein synthesis (Bergmann et al, 2000;Min et al, 2007). In addition to its IFN antagonistic activities, NS1 has recently been shown to actively suppress RNA silencing in plant, insect and mammalian cells (Bucher et al, 2004;Delgadillo et al, 2004;Li et al, 2004;Haasnoot et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…However, the majority of previous work has focused on the ability of NS1 to circumvent the host cell antiviral responses. This is achieved in a number of ways, including blocking 2Ј-5Ј-oligoadenylate synthetase (2Ј-5Ј-OAS) activation of RNaseL (18), limiting the induction of IFN-␤ by preventing the activation of transcription factors (19)(20)(21), interaction with the cellular protein retinoic acid-inducible gene product I (RIG-I) (22)(23)(24), blocking host cell mRNA polyadenylation (25,26), and blocking the PKR-mediated inhibition of protein synthesis (13,27). It has also been shown that NS1 prevents the maturation of human primary dendritic cells, thereby limiting host T cell activation (28).…”
mentioning
confidence: 99%